The Yi Music Writing Techniques of Jiaba Asan - Chen, Weixing; Chonpairot, Jarernchai (Journal of Roi Kaensarn Academi, 2024)
The title of this thesis is Yi music writing techniques of Jiaba Asan. The research objectives are: 1, Study about Yi music writing techniques of Jiaba Asan, 2, Analysis components of selected Yi music of Jiaba Asan. The research site is located in Butuo County, Liangshan Yi Autonomous Prefecture, Sichuan Province, China. Through the on-site interview of the key informant Mr. Jiaba Asan, and the use of musicology theory to analysis the two songs "Dream back to Nanzhao" and "Morning night", the method of on-site interview, questionnaire survey and collection of literature data, to obtain the research results. Through research, the author finds that: 1, Jiaba Asan uses Yi ethnic religious music and folk song materials to create song melodies, and writes lyrics using cultural themes such as Yi mythology, epics, and poetry. 2, Jiaba Asan uses electronic and ethnic instruments, as well as contemporary music harmony to arrangement songs, and uses computer music software to record songs. 3, Jiaba Asan's childhood memories and observations and perceptions of life are the source of song creation. This research emphasizes the innovation of Yi music, and puts forward specific implementation suggestions for the reference of relevant personnel.